PENGARUH PENAMBAHAN JUS KULIT PISANG KEPOK (Musa acuminate) TERHADAP KESUKAAN KEEMPUKAN DAN KANDUNGAN PROTEIN TERHADAP RENDANG DAGING SAPI - Sofyan Ali Mahmud; Edya Moelia Moeis; Risma Novela Esti (Universitas Islam Balitar, 2020)
This study aims to determine the effect of adding kepok banana skin juice (Musa Acuminate) on the softness and protein content of beef rendang after cooking. This type of study is experimental with a complete randomized controlled trial (RAL) consisting of 4 treatments 5 times. The treatment used is P0 (0% / 500g meat) as control, P1 (5% / 500g meat), P2 (10% / 500g meat), P3 (15% / 500g meat). The research parameters were the softness of meat and protein after cooking, the data were analyzed using Anova (Variant Analysis) and Duncan further test with 0.05 level. The results of the softness test showed that the addition of kepok banana skin juice (Musa Acuminate) had an effect on the softness with Fhitung greater than Ftabel (3.51> 3.24). the same results produced by protein test analysis results showing Fhitung is larger than Ftabel (34.07> 3.24). Followed by further tests Duncan at the level of 0.05 softness preference test showed that P0, P1, P2 treatment had no real effect, and at P3 treatment there was a significant effect. Further tests of Duncan protein after cooking show that each treatment is very different. It can be concluded that the addition of kepok banana skin juice has a real effect on the tenderness of softness and protein from beef rendang.